Dinamika Kolaborasi Dalam Pendidikan Karakter: Wawasan Dari Sekolah Dasar Tentang Keterlibatan Orang Tua Dan Guru - Iman Subasman; Dian Widiantari; Rusi Rusmiati Aliyyah (Departement of Mathematics Education, 2024)
This study investigated the implementation and perception of character education programs in three elementary schools in West Java, utilizing a qualitative case study methodology. Through in-depth interviews, participatory observation, and document analysis, the study unpacks the practice of teaching character values by teachers and how they are accepted by students and parents. With a rigorous selection process, three primary schools were selected as research sites to capture the diversity of character education approaches. Key findings reveal that, although character education programs have been successfully integrated into school curricula and activities, there are significant challenges with regard to consistency of implementation and diverse perceptions among stakeholders. The effectiveness of the program is measured by changes in student behavior, increased moral awareness, and increased involvement of parents in their children's character education. The study underscores the importance of effective communication and collaboration between schools and families, and emphasizes the need for continuous teacher training to improve the quality of character education implementation. The results of this study provide valuable insights into existing best practices and challenges, contribute to the educational literature and offer recommendations for the further development of character education programs.